A conceptual framework for treating jaw deformities in patients with abnormal condyles: preservation versus replacement of the glenoid fossa–disc–condyle–ramus. Issue 1 (January 2022) - Posnick, J.C.; Kaban, L.B.
Abstract: This article outlines a conceptual approach to the reconstruction of jaw deformities associated with abnormalities in the mandibular condyle. The authors describe a hierarchy of reconstruction, emphasizing use of the least invasive and progressing to the most complex and invasive techniques, depending on the nature and severity of the underlying deformity, prior operations, patient age, and stage of growth. Consider joint preservation orthognathic surgical correction, followed by biological techniques for replacement of the condyle, and avoid replacing a functional temporomandibular joint based only on radiographic remodeling and concerns about potential future flare-ups of disease based on anecdotal data.